MATHEMATICAL MODELLING OF THE FACTORS OF LAND USE OF THE OBJECTS OF THE NATURE RESERVE FUND OF THE REGIONS - Mamonov, K.; Viatkin, R.; Shterndok, E.; Shterndok, A. (Municipal economy of cities. Series: «Economy science», 2024)
It has been proven that the land use level of the nature reserve fund objects is decreasing, and their condition is being disturbed based on unjustified construction, in particular. In this context, forming a quantitative basis for decision-making through implementing mathematical modelling of the land use factors of the nature reserve fund objects of the regions is particularly relevant. As a result of the generalisation of theoretical approaches, we proposed a definition of ‘land use monitoring of the nature reserve fund objects of the regions’ as a set of legal, constructive, complex, organisational, functional, and instrumental directions aimed at the formation of informational, analytical, and spatial support regarding the state and level of land use of the nature reserve fund objects at the regional level using mathematical modelling methods, which creates a quantitative basis for permanent tracking and control over the use of the nature reserve fund objects. The purpose of the study is to use mathematical modelling tools to establish cause-and-effect relationships between the factors of land use of the nature reserve fund objects of the regions. In this context, the study has solved the following tasks: highlighting the practical aspects of mathematical modelling of the factors of land use of the nature reserve fund objects of the regions; characterisation of the adequacy criteria of the established relationships between the integral indicator of the level of land use of the nature reserve fund objects of the regions and factors using the method of neural networks. The results of mathematical modelling allow for forecasting changes in the integral indicator of the level of land use of the nature reserve fund objects of the regions depending on the relevant factors and for offering scientifically based recommendations for the development and implementation of monitoring of the formation of land use of the nature reserve fund objects of the regions. The conducted analysis of the adequacy of the developed mathematical models of the influence of factors on the integral indicator of the level of land use of the nature reserve fund objects of the regions using the neural network method made it possible to confirm the completeness and reliability of the established relationships based on the low values ​​of the relative error of the test sample.